The Circus of Human Trafficking - Dharel, Milan (Kathmandu School of Law Review, 2012)
Human Trafficking has been in debate of development and human rights interventions for past many years. With the changes in social political and economic context the understanding and responses on combating human trafficking has been widening. Yet, the debate has been heavily influenced by human trafficking for sexual slavery and later on labor exploitation followed by organs transplantation. Anti Human trafficking interventions in Nepal is still much influenced by protectionist conception and undermining the global economics and politics related to human trafficking concern. In addition, the interventions are much more focused on boarder control and punishing the petty criminals. The circus of human trafficking, despite of protest, control and protection interventions, have been in existence with flourishing market and effective influence. The paper discusses that, to stop the circus of human trafficking, interventions should go beyond romantic heroism, petty criminal boarder control action and further need to claim accountability of larger actors sitting far behind the curtains.